Fragile settlements Aboriginal peoples, law, and resistance in South-West Australia and prairie Canada - Nettelbeck, Amanda; Smandych, Russell Charles; Knafla, Louis A. 1935-; Foster, Robert 1958- (UBC Press, 2016)
"Fragile Settlements compares the processes through which colonial authority was asserted over Indigenous people in southwest Australia and prairie Canada from the 1830s to the early twentieth century. At the start of this period, there was an explosion of settler migration across the British Empire. As a humanitarian response led to the unprecedented demand for land, Britain's Colonial Office moved to protect Indigenous peoples by making them subjects under British law. This book examines the tensions and contradictions that emerged as colonial actors and institutions--including government officials, police, courts, churches, and philanthropic organizations--interpreted and applied the principle of law in their interactions with Aboriginal peoples on the ground. As a comparative work, Fragile Settlements highlights important parallels and divergences in the histories of law and Indigenous-settler relations across the Anglo-colonial world. It questions the finality of settler colonization and contributes to ongoing debates around jurisdiction, sovereignty, and the prospect of genuine Indigenous-settler reconciliation in Canada and Australia."--